The Intersection of Gender, Class, and Culture: An Intersectional Feminism Study of Career Women in Surabaya - Nawang Wulan; Ahmad Ridwan; Permata Ayu Widyasari (Jurnal Partisipatoris, 2025)
This study aims to explore how career women in Surabaya navigate the intersection of gender, social class, and culture in their daily lives. The focus of this research is to understand the strategies, barriers, and meanings that emerge from women's negotiation process between domestic expectations and professional identity amidst the urban patriarchal social context. Using an intersectional feminism theoretical framework, this qualitative study involved five female informants aged 26-40 years who work as teachers, administrators, store managers, head store managers, and nurses. Data were collected through semi-structured in-depth interviews and participatory observation, then analyzed using the interactive model of Miles, Huberman, and Saldana, which includes data condensation, data display, and conclusion drawing and verification. The results show that career women in Surabaya experience layered pressures originating from gendered cultural norms and social classes. Nevertheless, the informants demonstrate agency through subtle resistance, strategic time management, and reinterpretation of traditional values that strengthen their professional and personal identities. This finding confirms that women's empowerment can grow from within the existing social system through awareness, adaptation, and collective solidarity. In conclusion, career women in Surabaya are not passive subjects of patriarchy, but active social agents who continuously redefine the meaning of women and independence in modern urban life.